Computed Tomography Features and Clinicopathological Characteristics of Gastric Sarcomatoid Carcinoma - Liu, Yi-yang; Liang, Pan; Feng, Kai-xiang; Chen, Kui-sheng; Yue, Song-wei; Ji, Jiang; Li, Wei-wei; Zhao, Xi-tong; Gao, Jian-bo (Frontiers in Oncology, 2020)
Purpose: Gastric sarcomatoid carcinoma (GSC) is a very rare malignant tumor. The purpose of this study is to describe the clinical, computed tomography (CT), and pathologic features of GSC to increase awareness of this entity. Methods: The CT features and clinical data of 5 patients with pathologically documented GSC were retrospectively analyzed and compared with the corresponding data of gastric adenocarcinoma and lymphoma. Results: Among the 5 patients, 4 were male, and 1 was female. The median age was 59 years. Of the 5 cases of GSC, 3 were in the gastric fundus and cardia, 1 was in the gastric body, and 1 was in the gastric fundus. The gastric wall had local thickening in 4 cases and mass formation in 1 case, with stenosis and deformation of the adjacent gastric cavity. The long-axis diameter of the lesions ranged from 1.4 to 10.2 cm (mean, 4.97 cm) and was <10 cm in 4 cases and >10 cm in 1 case. The tumor showed predominantly inhomogeneous density, with radiodensity values ranging from 30 to 53 HU. In addition, ulcers with an irregular base and slightly raised borders were observed in 4 of 5 cases. After an injection of contrast material, heterogeneous (n=4) or homogeneous (n=1) enhancement was observed. After contrast medium injection, obvious enhancement was seen in 2 cases, and moderate enhancement was seen in 3 cases; the peak tumor signal was observed in the portal phase. Two of the patients demonstrated evidence of lymph node involvement, and in one patient, the boundary between the lesion and the left lobe of the liver was unclear, with low attenuation in the right lobe of the liver with circular enhancement. The remaining two patients showed no evidence of metastasis. Conclusion: Although GSC is extremely rare, it should be considered in the differential diagnosis of gastric adenocarcinoma and lymphoma. CT findings, combined with patient age and sex, can provide support for the diagnosis of GSC. However, the final diagnosis must be confirmed with histopathology.